Surface modification of poly(dimethylsiloxane) through oxygen and nitrogen plasma treatment to improve its characteristics towards biomedical applications. (4th September 2015) - Gomathi, N; Mishra, I; Varma, S; Neogi, S
Abstract: Polymeric materials successfully applied in biomedical applications have an issue of poor surface properties which may restrict their applications as biomaterials. The present paper aims to study the effect of oxygen and nitrogen plasma treatment on physico-chemical properties of poly(dimethylsiloxane) (PDMS) and enhancement in its biocompatibility. Various characterization techniques including Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy, scanning electron microscopy (SEM), atomic force microscopy were used to evaluate the changes in surface chemistry and morphology of plasma treated PDMS. Changes in the wettability after plasma treatments and the effects of ageing on wettability were studied by contact angle measurement. Ageing studies showed that the contact angle was stable after two hours. The effect of plasma treatment on biocompatibility was studied through cell adhesion and MTT using 3T3 fibroblast cells. Morphology of cells obtained through SEM was analyzed using ImageJ software. Among the different treated and untreated samples, substantial enhancement in biocompatibility was observed for nitrogen plasma treated PDMS for 5 min in terms of highest cell area observed from cell adhesion test and highest cell viability observed from MTT test. This may be probably due to its highest polarity (0.4) and surface energy (33.3 N mm −2 ) with a moderate surface roughness ( R rms  = 100.24 nm) among the other treated and untreated samples.